Syeikh Abdul Qadir bin Abdul Muttalib Al-Mandili: Sumbangan Dalam Ilmu Tauhid, Fiqah dan Tasawuf - Asyraf, Abd Ghani @ Mohd Azmi (2013)
Sheikh Abdul Qadir bin Abdul Muttalib al-Mandili was a renowned scholar who was instrumental in developing religious knowledge in Malaysia. He was regarded as a controversial religious scholar (ulama) because of his decrees (fatwas) on jurisprudence and nationhood. Nevertheless, his concern in addressing the problems of society is well documented through his works mainly in three important fields of Islamic knowledge namely monotheism, jurisprudence and sufism. Sheikh Abdul Qadir bin Abdul Muttalib al-Mandili was an exceptional scholar who mastered three important knowledge simultaneously in his time. The objective of this study is the first to present a biography and background that influenced him to become a well-known scholar in the Malay world and in Mecca. Second, to find out his contributions in expanding the knowledge of monotheism, jurisprudence and sufism to the community and third, to explore his thinking in highlighting ideas to address current issues faced by Muslims. This study used qualitative research methods. The data was obtained through library research and field studies. Interviews with scholars related to Sheikh Abdul Qadir bin Abdul Muttalib al-Mandili were also conducted. The research findings showed that family background, education and society had made him a well-known and respected scholars. The study also found that he was able to contribute simultaneously in all three areas, namely monotheism, jurisprudence and sufism. This had a profound effect in the field of social science, economics and politics. Meanwhile in highlighting his ideas to address current issues of Muslims, he referred to the Quran, hadith, ijma and analogies as the basic insights of his thinking besides considering the views of the scholars on every issue that happened.